ANALYSIS OF ENERGY EFFICIENCY RATIO (EER) IN AIR CONDITIONER (AC) TYPE SPLIT - Yolanita Fani; Ilham Arnif (VANOS Journal of Mechanical Engineering Education, 2019)
Cooling system is something that is already familiar to the people of Indonesia, both in domestic and industrial use. The cooling system functions to reduce the temperature of a room so that the temperature is as desired. The development of air conditioners is increasingly modern. The use of air conditioners (AC) is growing rapidly so that the CFCs produced affect the environment which can cause the ozone layer to be damaged and cause global warming. Therefore, there is a need for research related to the level of energy use. This study discusses the Energy Efficiency Ratio test to realize a government program that is "one family one number testing". Retrieval of data in this report is by testing the split type air conditioner, where this test aims to obtain an energy-saving star label on the air conditioner. All tests are carried out at the AC Chamber Laboratory located at the Center for Energy Conversion Technology (B2TKE) - BPPT which is a professional energy conversion testing center in Indonesia. The testing process is carried out in a structured way from initial checking of test materials, preparation of tests, testing to analysis of test results. Based on the test analysis results, it can be concluded that the Energy Efficiency Ratio (EER) value to get the energy saving sign star label and the test results obtained the Energy Efficiency Ratio (EER) value of 11,805 Btu / h and get a four star.